Estrategia de marketing para el fortalecimiento del comercio electrónico del mega almacén y mueblería milagro”, año 2023. - Molina Veliz, Adasis Illonit (2024)
The following research work demonstrates that by analyzing, describing and investigating, it is possible to identify weaknesses and strengthen them. Therefore, this study begins by carefully detailing the problems facing the company. At the same time, a solution is proposed that consists of creating a social network to strengthen the image and corporate identity of the company. The implementation of the social network managed to change people's perception of the brand, ensuring that corporate values are clearly identified and, above all, that there is a notable difference compared to the competition. Through these new strategies, the aim is to increase sales and, therefore, obtain better profits, which has had a significant impact. The methodology used in this research study was analytical and descriptive, specifically focused on the field study. The combination of both approaches allowed us to observe, analyze, synthesize and describe the current situation of the company Mega Almacén y Mueblería Milagro. Subsequently, with the collection of information, it was possible to develop the social network and design the necessary strategies and actions to improve